Analysis of Religiosity, Customer Perceptions and Income Levels on the Decision to Choose Savings and Loans Cooperatives and Sharia Financing - M. Trihudiyatmanto; Abiodun Babatunde Onamusi (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Purpose - This study aims to determine the influence of religiosity, customer perceptions and income level on the decision to choose Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) Melati, Sapuran branch in Wonosobo.Methodology - The analysis in this study uses multiple linear regression analysis to answer the questions in this study. This study used a total sample of 99 respondents to obtain research data.Results - The results of this study indicate that customer perceptions and income levels have a positive effect on the decision to choose KSPPS Melati. While the religiosity variable has no effect on the decision to choose KSPPS Melati.Implications - This study uses primary data obtained from respondents' answers through questionnaires distributed to respondents.Originality - Future research is expected to be able to add or replace variables in this study, in order to increase interest in choosing KSPPS Melati.